The impact of substance abuse on the development of active tuberculosis in HIV positive patients depending on their CD4 count - E. I. Kulаbukhovа; V. N. Ziminа; I. P. Chernovа; T. A. Murzаkovа; V. V. Belyaevа; А. V. Krаvchenko (Туберкулез и болезни лёгких)
The objective of the study: to assess the risk to develop active tuberculosis in HIV infected patients with history of substance abuse taking into account their CD4 count.Subjects and methods. A retrospective case-control study was conducted with enrollment of 171 patients: HIV Group included 85 persons, while TB/HIV Group – 86 persons. For screening for chronic alcohol/narcotic intoxication, the CAGE questionnaire was used, and tobacco dependence was detected according to the criteria of World Health Organization. CD4 counts were obtained by the retrospective analysis of medical records. The impact of the studied risk factors on the development of tuberculosis was estimated by calculating the odds ratio with the calculation of the 95% confidence interval.Results. Statistically significant association with the development of active tuberculosis was obtained for all factors studied (tobacco smoking: OR = 8.7, 95% CI 3.6-21.6, p = 0.01; chronic alcohol and narcotic intoxication: OR = 3.5, 95% CI 1.8-6.5, p = 0.001 and OR = 2.5, 95% CI 1.1-5.4, p = 0.026, respectively). In the group of patients with CD4 count above 200 cells/µL, there was a confident effect of smoking and clinically significant substance abuse on the risk to develop active tuberculosis, and the power of their effect increased: for tobacco smoking OR = 12; 95% CI 1,5-98,7, p = 0.012; for drug abuse, OR = 4.8, 95% CI 1.7-13.4, p = 0.002. The tendency of chronic alcohol intoxication providing impact on the risk to develop tuberculosis in patients with CD4 count above 200 cells/μl persisted, but there was no statistically significant relationship in calculating the odds ratio OR = 3.1, 95% CI 3.1–9.6, p = 0.082. The obtained data allow considering people living with HIV and possessing history of substance abuse as a group facing the high risk to develop tuberculosis in need close follow-up aimed to prevent tuberculosis.